Trends and risk factors of care-seeking delay among students with pulmonary tuberculosis in Wuhan, China, 2012–2025 - Zhengbin Zhang; Wei Zhang; Gang Wu; Jianjie Wang; Aiping Yu; Jun Chen; Zhouqin Lu; Guiyang Wang; Tiantian Wang; Xiaojun Wang; Jing Hu; Yuehua Li (Frontiers in Public Health, 2026)
Background Care-seeking delay among students with tuberculosis (TB) poses a significant barrier to school-based TB prevention and control. Such delay facilitates the transmission of Mycobacterium tuberculosis in high-density populations and frequently leads to cluster outbreaks in schools. This retrospective study examined the prevalence, temporal trends, and risk factors of care-seeking delay among student TB patients in Wuhan, China, over a 14-year period (2012–2025). Methods This retrospective study used data from the Chinese National Tuberculosis Information Management System (N-TBIMS). All registered student pulmonary tuberculosis (PTB) cases in Wuhan from January 1, 2012, to December 31, 2025, were included. Multivariable logistic regression was used to identify independent risk factors for delay. Results A total of 4,920 student PTB patients were enrolled (median age: 19 years, IQR: 17–21,60.54% male). The median time to care-seeking was 9 days (IQR: 3–21), and 37.72% delayed care-seeking for ≥14 days. The delay proportion remained stable at approximately 38.84% during 2012–2019, dropped sharply to 26.55% in 2021, then rebounded to 48.47% in 2022 and reached 55.57% by 2025. Female students experienced a dramatic increase, with rates exceeding 50% during 2022–2025, while male students remained relatively stable. Children aged 3–11 years had the highest delay proportion (55.47%), peaking at nearly 80% in 2023. Multivariable analysis identified key risk factors: non-Han Chinese ethnicity (OR = 2.530, 95% CI: 1.702–3.763, p = 0.001), trace detection mode (OR = 2.875, 95% CI: 1.991–4.152, p = 0.001), referral detection mode (OR = 1.670, 95% CI: 1.174–2.376, p = 0.004), and Sputum bacteria-positive (OR = 0.869,95% CI: 0.764–0.990, p = 0.035) compared to Sputum bacteria-negative. Adolescents aged 12–17 years (OR = 0.499,95% CI: 0.333–0.746, p = 0.001) and young adults aged 18–22 years (OR = 0.538,95% CI: 0.362–0.801, p = 0.002) had approximately 50% lower risk compared to children aged 3–11 years. Conclusion Care-seeking delay (≥14 days) affected 37.72% of student TB patients in Wuhan. The COVID-19 pandemic had a dual impact: strict NPIs in 2020–2021 transiently reduced delays, while post-pandemic health-system strain drove a rebound exceeding pre-pandemic levels. Four distinct risk factors for delay emerged: non-Han students, children aged 3–11 years, passively detected cases via contact tracing or referral, and sputum bacteria-positive patients. Targeted health education, school-based symptom screening, expedited diagnosis after referral or tracing, and multisectoral collaboration among schools, families, and TB control centers are urgently needed to reduce delays and avert school-based outbreaks.